We the people : a brief introduction to the Constitution and its interpretation - Dahlin, Donald C. (Palgrave Macmillan, 2012)
We the People is, simply put, about the U.S. Constitution. The author takes an analytical approach to existing scholarship and presents a limited number of landmark Supreme Court decisions in a way that makes this important material more accessible to the general reader. Dahlin emphasizes, as the Preamble states, that it is We the People who have created the Constitution, and so We the People today need to have a solid understanding of 'our' document if we are to participate intelligently in the many important contemporary debates about what the Constitution does or does not mean and does or does not allow.